Using Diacritics in the Arabic Script of Malay to Scaffold Arab Postgraduate Students in Reading Malay Words (Malaysian Journal of Learning and Instruction, 2015)
Purpose â€“ This study aims to investigate the use of diacritics in the Arabic script of Malay to facilitate Arab postgraduate students of UKM to read the Malay words accurately. It is hypothesised that the Arabic script could facilitate the reading of Malay words among the Arab students because of their earlier exposure to the Arabic script in comparison to the Romanised script. Method â€“ Twelve Arabic fi rst language speakers participated in a reading experiment that used DMDX, a Win 32-based display system for psychological experiments, to investigate whether or not Arabic vowel diacritics can facilitate Arabic fi rst language speakers to read Malay words accurately. A total of 100 Malay bi-syllabic words were used as stimuli in three different forms: 1) Arabic script without diacritics; 2) Arabic script with diacritics; and 3) Romanised script. The participantsâ€™ responses and reaction times were recorded to analyse accuracy and speed. Findings â€“ Arabic first language speakers were more accurate when reading words in Arabic script of Malay with diacritics and when reading Romanised script than when reading Arabic words without diacritics. Arabic speakers read Malay words faster in Arabic script without diacritics and in Romanised scripts than when reading words in Arabic script with diacritics. Significance â€“ This study shows that the use of a more familiar script to a certain extent does facilitate language learners to produce the target language more accurately compared to using a less familiar script. Hence, educators should explore any possible means to scaffold learners in their learning process.